STUDY ON DAMPING CHARACTERISTICS OF LONGERON TUBES FOR NOISE SPECTRA COMPUTING ACCURACY INCREASE - Sergey A. Shamshura (Advanced Engineering Research, 2012)
Studies on the noise generation pattern under the long co mponent milling are resulted. It is shown that the noise abatement can be achieved through the choice of the longeron and support unit loss factors.